PARCS cross-section library generator; part one: Development and verification. (January 2015) - Porhemmat, M.H.; Hadad, K.; Faghihi, F.
Abstract: In this paper, a novel method for generating the PMAXS format cross section of the PARCS code using WIMSD-5 lattice code is presented, and examined in a VVER-1000 core. This claim is implemented by writing a FORTRAN-90 program called SARCS (S hiraz UniversityA dvancedC rossS ection library) which produce input, and execute/or reformat WIMSD-5 output into PMAXS file format of the PARCS code. Each fuel assembly of a VVER-1000 core is modeled by WIMSD-5; the group constants consistent with GenPMAXS are extracted and then the PMAXS file is produced. Our generated libraries are verified by modeling VVER-1000 Bushehr Nuclear Power Plant (BNPP) core during Hot Zero Power (HZP) as well as Cold Zero Power (CZP). Comparison of the PARCS results with the Final Safety Analysis Report (FSAR) of the BNPP and its Neutronics Album is presented herein. Highlights: Development of a new and convenient method to generate PMAXS cross section library of LWRs for PARCS simulation. The PMAXS library is extendable to normal and any transient conditions analysis of LWR's. Verification of generated PMAXS formatted cross section library using a VVER-1000 PARCS and WIMSD-5 models. Developing a PARCS model for verifying VVER-1000 Neutronic Album in the beginning of cycle. The generated PMAXS library is updateable with IAEA cross section updates.